(untitled) (Konferensiyalar | Conferences, 2024)
In todays rapidly developing internet-dependent world full of technological advances. Although, teenagers on social media platforms much of their time observing the lives and images, leading to constant comparisons, which can damage self-esteem and body damage .The article provides information about negative consequences associated with social media overuse. In the vast expanse of the digital landscape, where pixels dance across screens and virtual connections span continents, lies a realm that holds immense sway over the hearts and minds of the young: social media. With its siren call of likes, shares, and comments, social media has emerged as both a beacon of connectivity and a crucible of influence, shaping the attitudes, behaviors, and identities of an entire generation. As the digital natives of today navigate the uncharted waters of the online world, the profound impact of social media on young people has become a subject of intense scrutiny and debate.